2010
DOI: 10.1038/aps.2010.77
|View full text |Cite
|
Sign up to set email alerts
|

Morin exerts neuroprotective actions in Parkinson disease models in vitro and in vivo

Abstract: Aim: To investigate the neuroprotective effects of morin on 1-methyl-4-phenylpyridinium ion (MPP + )-induced apoptosis in neuronal differentiated PC12 cells as well as in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of Parkinson disease (PD). Methods: PC12 cells were challenged with MPP + in the presence or absence of morin. Cell viability was determined using MTT assay. Cell apoptosis was measured using flow cytometry. Generation of reactive oxygen species (ROS) was assayed using fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…This kind of dose-response relationship has been reported previously [21,35,36] . It is common that a chemical binds to two or more targets/receptors with different affinities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This kind of dose-response relationship has been reported previously [21,35,36] . It is common that a chemical binds to two or more targets/receptors with different affinities.…”
Section: Discussionsupporting
confidence: 85%
“…It is well known that rotenone, 6-OHDA, and MPP + cause neurotoxicity in cells in vitro [21,22] ; thus, our previous data suggested that Bu-7 may have a positive effect on anti-apoptosis and mitochondrial protection. Therefore, in our present study, we utilized rotenone to create an in vitro cell model to study the protective effects of Bu-7 in PC12 cells and tried to find the possible underlying mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…Acacetin at a dose of 200 nM protected in vitro and in vivo mesencephalic cells against MPP + insults with decrease of NO, prostaglandin E2 (PGE2), and TNF-α. 24 Hydroxylation of acacetin in C5′ yields diosmetin (CS 3.12), which at a dose of 500 nM protected hippocampal neurons against glutamate insults. 24 Hydroxylation of acacetin in C5′ yields diosmetin (CS 3.12), which at a dose of 500 nM protected hippocampal neurons against glutamate insults.…”
Section: Benzopyronesmentioning
confidence: 99%
“…Also, many studies have demonstrated that polyphenols sensitize cancer cells to chemotherapy via effects on survival and growth signaling pathways [35, 36]. Moreover, morin hydrate has been shown to exert a neuroprotective effect via its antioxidant properties in mouse models of Parkinson’s disease [37] and against excitotoxic neuronal death in culture [38]. However, the relatively high IC 50 in live cells and in extracts would not be conducive to using morin hydrate to inhibit MPG-induced carcinogenesis, resistance to chemotherapy, or alkylation damage-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%